Studies on Adsorption of Fluorescein Dye from Aqueous Solutions Using Wild Herbs - Ghadah M. Al-Senani; Nada S. Al-Kadhi (International Journal of Analytical Chemistry)
The adsorption of fluorescein dye (FD) on wild herb microparticles (Juniperus (JH) and Solenostemma argel (Del) Hayne (SH)) was studied to elucidate the changes in adsorption behavior with various parameters, such as initial concentration, adsorbent dosage, pH, contact time, and temperature. It was determined that the adsorption percentage of JH for FD was as high as 85.5%, which was higher than that of SH (71.9%). The morphologies of JH and SH were analyzed using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM) analyses. The JH and SH adsorbents contained different functional groups, which were involved in the binding of the FD molecules during adsorption. The XRD patterns of JH and SH confirmed the presence of a combination of amorphous and crystalline phases in their structures. The SEM images of the surface of JH revealed the presence of deep pores ranging in size from 1.9 to 3.5 μm, while SH contained smaller pores ranging in size from 130 to 350 μm, which could help absorb large quantities of FD. The Freundlich model fitted the adsorption isotherms better than the Langmuir model. The values of the Freundlich equilibrium coefficient and separation factor ranged from 1 to 2 and from 0 to 1, respectively. The maximum adsorption capacities of JH and SH were determined to be 2.91 and 2.565 mg/g, respectively. Four kinetic models were used to analyze the experimental data, and it was determined that the pseudo-second-order kinetic model best described the adsorption process, which involved chemical adsorption and the internal diffusion. Thermodynamic parameters, including the enthalpy, entropy, and Gibbs free energy, were calculated. These parameters indicated that the adsorption of FD on JH was spontaneous and endothermic and the adsorption of FD on SH was unspontaneous and exothermic.